Empowering Blind Children through Future Technology: Protective Factors Associated with AI-Based Audio and Braille Dictionaries in English Learning - Yuli Nuranawati; Urai Salam; Venny Karolina; Aunnurrahman Aunnurrahman; Eka Ariyati (LP. Ma'arif Janggan Magetan, 2026)
This study investigates how an AI-integrated Braille and audio dictionary supports academic resilience among blind students learning English. Employing a qualitative phenomenological design, the study involved seven blind tenth-grade students from two special schools in West Kalimantan, Indonesia, along with parents, English teachers, and school principals. Data were gathered through in-depth interviews, focus group discussions, classroom observations, and documentation, then analyzed thematically using Masten’s resilience theory, Ungar’s resource negotiation perspective, and Bronfenbrenner’s Ecological Systems Theory. Findings reveal three interrelated themes: (1) AI-supported audio features fostered individual protective factors, including persistence, self-efficacy, and adaptive problem-solving; (2) the Braille-audio integration functioned as a protective technological resource by enhancing multisensory learning, autonomy, and pronunciation accuracy; and (3) resilience was strengthened through teacher and parental environmental support. The study proposes a Digital Resilience Framework highlighting how internal capacities, accessible technology, and ecological support interact to sustain blind learners’ engagement in English learning. These findings contribute to inclusive education literature by demonstrating that assistive AI technologies serve not only as learning tools but as resilience-enhancing resources for students with visual impairments.